Assessment of indicators of children education in Serbia with implication to the health literacy: Assessment of indicators of children education in Serbia with implication to the health literacy - Maricic, Milena; Trbovic, Verica; Pavlovic Jugovic, Katarina; Jezdimirovic, Danijela; Antic, Gordana; Pazun, Vanja; Ilić, Slađana; Jelić, Milena; Stojanovic, Goran (Medicinski časopis, 2025)
Introduction: Access to primary education is the basic right of every child. The aim of the work is to assess the status of the share of children of official primary school age who are not enrolled in school and sex differences, as well as the children enrolled in pre-school education, in Serbia, over a period of 15 years. Method: The research was conducted as an observational epidemiological study. The indicators analysed in this research are the "Share of children of official primary school age who are not enrolled in school" and the indicator "Gross rate of enrolment in preschool education", observation period from 2006 to 2021. Results: The average percentage of male children outside primary school education was 2.18%, while the percentage of female children was 2.14%. The lowest percentage was observed in 2006, and the highest increase in 2010. The linear regression showed a positive trend for both sexes. There was a significant difference in the percentage of boys and girls outside primary school education in Serbia. On average, almost 60% of children were enrolled in preschool institutions in Serbia, and this increase has shown a significant positive trend over observed time.  Conclusion: Serbia stands at a crossroads where continued progress in education could lead to major gains in health literacy and equity. Addressing existing disparities with targeted and inclusive educational policies will be essential not only for achieving educational justice but also for building a healthier and more informed society.
Keywords: children, education, indicators, Serbia, health literacy